Microbiological study of fish from the rural market of Katana on the edge of Kahuzi-Biega National Park, South Kivu Province, DRC - Lushombo Bunani; KAZADI MINZANGI; Kabongo Kanimba; Ololo Tshiamala; Efoloko Bokungu; Bahizire Kayeye; Valery Byenda Badesire; Zigashane olivier; Mutabazi Muhindo (Orapuh Journal)
Introduction